Boredom, motivation, and perceptions of pain: Mechanisms to explain the effects of self-control exertion on subsequent physical performance. (November 2022) - Hunte, R.; Cooper, S.B.; Taylor, I.M.; Nevill, M.E.; Boat, R.
Abstract: Objectives: Prior self-control exertion has been shown to have a detrimental effect on subsequent physical performance. However, some potential underpinning mechanisms of the effect have yet to be examined. The present study explored whether exerting self-control reduces subsequent physical performance; and also examines the role of boredom, motivation, perceptions of pain, and sustained attention as mechanisms to explain these performance effects. Methods: In a within-subjects order-balanced crossover design, 63 participants completed a self-control exertion task (incongruent Stroop) and non-self-control exertion task (congruent Stroop) for 4 min. Immediately after, participants completed a wall-sit task until volitional exhaustion. Task-specific boredom was measured following the Stroop task and following the wall-sit task. Participants' perceptions of pain and motivation were measured every 30 s during the wall sit task. Upon completion of the wall-sit, participants completed a test of sustained attention. Results: Following the self-control exertion task, participant's wall-sit performance time was reduced (136 ± 62 s), compared to when they completed the non-self-control exertion task (144 ± 57 s, p  = 0.05, d  = 0.14). Participant's task related boredom was significantly higher during the non-self-control exertion task (4.30 ± 1.23), compared to the self-control exertion task (3.82 ± 1.22) ( p  < 0.001, d  = 0.39); but boredom was not different during the wall-sit task ( p  = 0.79). Prior self-control exertion also led to increased overall perceptions of pain ( p  = 0.02) and reduced overall ( p  = 0.01) and initial ( p  = 0.02) motivation during the wall-sit task. However, no differences in initial perceptions of pain ( p  = 0.16) or sustained attention (response time, p  = 0.99; response accuracy, p  = 0.78) were observed. Additional within-subjects mediation analysis revealed that differences in wall-sit performance time could not be explained by differences in task related boredom during the Stroop task, overall perceptions of pain, or overall and initial motivation (all p >  0.05). Conclusions: The prior exertion of self-control resulted in a decrement in subsequent physical performance. Furthermore, individuals' perceptions of task related boredom were higher during the non-self-control exertion (congruent Stroop) task, whilst overall perceptions of pain were higher, and initial and overall motivation were lower, following the self-control exertion (incongruent Stroop) task. However, mediation analysis revealed that these mechanisms did not explain the difference in wall sit performance time between the conditions. Highlights: Self-control exertion reduced subsequent wall-sit task performance. Perceptions of task related boredom were higher during the non-self-control exertion task. Overall perceptions of pain were higher following self-control exertion. Initial and overall motivation were lower following self-control exertion.